Estimation of Radiation Risk Due to Exposure to Terrestrial Radiation - , U. L. Anekwe; , S. O. Ibe (Archives of Current Research International, 2017)
An in-situ measurement of background radiation level of Ewoi community in Ogbia Local Government Area of Bayelsa State Nigeria was done using two radiation meters (Digilert-200 and Radalert-100). Exposure rate measured ranged from 0.010 to 0.028 mRh-1 with mean value of 0.016 mRh-1. The mean value of absorbed dose was 128.67 nGyh-1 while the mean indoor and outdoor annual effective dose equivalents were 0.40 mSvy-1 and 0.13 mSvy-1 respectively. The mean excess lifetime cancer risk estimated from both indoor and outdoor effective doses were 1.0 × 10-3 and 0.33 × 10-3 respectively. It was observed that all the radiological parameters estimated from the radiation exposure rate were higher than their world average values except the annual effective doses. The result of this study shows that Ewoi community recorded slightly high background radiation level and this may be attributed to oil and gas exploration activity in the area. The result of this work serves as radiological baseline data of the area for future studies